KEPEMIMPINAN DAN KEBIJAKAN PENDIDIKAN ISLAM - Fadhilatus Syarifah; Abd. Aziz; Nur Efendi (Prodi PAI Fakultas Tarbiyah IAI Sunan Giri Trenggalek, 2026)
This study aims to analyze the concepts of leadership and Islamic educational policy and their relationship to improving the quality of education. The study employed a qualitative approach with library research, drawing on relevant books, scientific journals, and official documents. Data collection was conducted through documentation studies, while data analysis employed content analysis. The results indicate that Islamic educational leadership is a key factor in the success of educational institutions. Leadership is not only defined as the ability to influence and direct, but also as a mandate that carries moral and spiritual responsibility. Furthermore, Islamic educational policy serves as a strategic instrument in directing the implementation of education to align with established goals. This policy is not merely administrative in nature but also embodies normative Islamic values ​​oriented toward the development of character, spirituality, and intellectual development of students. Leadership and Islamic educational policy have a complementary relationship. Effective leadership will result in appropriate and implementable policies, while good policies require strong leadership to ensure optimal implementation. Therefore, strengthening leadership and developing adaptive and sustainable Islamic educational policies are crucial steps in realizing quality Islamic education.